GRANICE UPRAWNIEŃ KIEROWNICZYCH PRACODAWCY W STOSUNKU PRACY - Duraj, Tomasz (Zeszyty Prawnicze, 2016)
THE LIMITS OF THE MANAGEMENT AUTHORITY IN THE EMPLOYMENT RELATIONSHIP Summary Management authority, which is guaranteed for the employer under the employment relationship with respect to employees, is an essential (necessary) feature of the employment relationship, which very often determines the identity of this relationship, distinguishing it from other legal forms of employment, especially those of a civil nature. The employing entity’s management authority must first of all be identified with the employer’s powers to influence the employee’s actions within the scope of the performance of work (in the work process) and the employee’s corresponding obligations to the employing entity regarding the work he is to perform. Using these powers, the employer specifies the employee’s obligations for the performance of the job, in particular its type, method, the time and place in which it is to be done, as well as the order and organization of the work process. According to the literature on the subject, the employer’s main powers of management include prescriptive rights (the core of management authority), which allow him to specify the employee’s duties by issuing binding instructions to him; punitive (disciplinary) powers associated with the use of disciplinary penalties; regulatory (legislative) powers, primarily to establish the regulations and other acts determining working order (in particular work schedules, holiday timetables etc.); and distributive power (the allocation of prizes and awards). The object of this study is to characterize the limits to the employer’s management authority in the employment relationship. The author concentrates on the limits defined by applicable law, the employment contract, the clause of compliance with socio-economic purpose, and the rules of social coexistence, as well as custom. The analysis of the limits of the employer’s management authority shows the importance of this issue, both in theoretical and practical terms. The appropriate configuration of these limits may help to solve one of the fundamental problems of modern labor law, which is to harmonize its protective and organizational functions.